Adult experience modifies attraction of the leafminer parasitoid opius-dissitus (hymenoptera, braconidae) to volatile semiochemicals - Petitt, F L; Turlings, Ted; Wolf, S P (My University, 1992)
Oviposition-experienced females of Opius dissitus Muesebeck, a braconid parasitoid of Liriomyza sativae Blanchard, preferentially landed on leafminer-infested rather than uninfested lima bean (Phaseolus lunatus L.) plants in a flight tunnel assay. Both naive and oviposition-experienced parasitoids responded strongly to odors of infested lima bean plants in a four-arm olfactometer in comparison with odors of uninfested plants, suggesting that volatile semiochemicals are used in host location. Parasitoids with an oviposition experience on lima bean ("lima-experienced") spent significantly more time in the infested odor than naive individuals, however, eggplant-experienced wasps did not spend significantly more time in the infested odor field than naive wasps. When parasitoids reared on leafminers in lima bean were provided a choice between the odor of infested lima bean and the odor of infested eggplant or cotton, naive and lima-experienced wasps preferred infested lima odor An oviposition experience on the other plant species resulted in a dramatic shift in preference. It was concluded that the experience effect was due, at least in part, to associative learning, as has been reported for other parasitoids. The parasitoids may perceive unconditioned stimuli during host contact and oviposition on an infested leaf and may associate those stimuli with volatile semiochemicals emanating from the leaf or host. Subsequently, the volatiles associated with the presence of hosts are used in directing the search for hosts.
Keywords: HYMENOPTERA; BRACONIDAE; OPIUS-DISSITUS; DIPTERA; AGROMYZIDAE; LIRIOMYZA-SATIVAE; SEMIOCHEMICAL; VOLATILE; FORAGING BEHAVIOR; ADULT; EXPERIENCE; LEARNING